Tekstinių ir diskursinių ribų laužymas Johno Banville’io romane Atėnė - Levina, Jūratė (Literatūra, 2015)
The article offers an intertextual analysis of John Banville’s novel Athena. Destruction of textual and discursive frames is shown a major technique most conspicuously manifested in two textual elements which do not have an identifiable function in the plot of the novel, i. e. in one of the main characters A. and in the descriptions of non-existing paintings by non-existing artists. Being at the centre of the narrative and yet having no function in the plot development, the figure of A. is shown to signal the essential significance of the principle of frame destruction at different textual layers and to manifest the impossibility of meaning in language and/or in art as signifying systems. The non-existing paintings, the names of their authors being the anagrams of ‘John Banville’ and their descriptions in various ways corresponding to John Banville’s writing, refer to Banville’s works; the way of reference calls for an intermedial interpretation which reveals the authorial reflection on (his own) art and, in connection with the analysis of the meaning of A., on the experience of the aesthetic, the immediate and self-reflective involvement of the reader being an essential part of the process. Hence the destruction of textual and discursive frames, manifested in John Banville’s Athena, is shown to be not an end in itself but rather a textual strategy of essential interpretative value.